2020
DOI: 10.5799/jcei/8264
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting COVID-19 in Morocco

Abstract: The COVID-19 has become a public health emergency of international concern. As of April 26, 2020, this pandemic has caused in Morocco more than 4065 confirmed infections and more than 161 reported deaths. To mitigate this epidemic threat and act quickly, it is very important to monitor and analyze changing trends and predict what might happen in the future. The main objective of this paper is to develop a successful prediction. We used in this study at the end of each week the TBATS model to forecast confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…These measures have helped to flatten the curve of contaminated cases relative to neighbouring countries (Sebbani et al, 2020), but the prospects for the spread of the pandemic remain alarming (Layelmam et al, 2020) and the socio-economic impacts have been as significant as those identified internationally (Nicola et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…These measures have helped to flatten the curve of contaminated cases relative to neighbouring countries (Sebbani et al, 2020), but the prospects for the spread of the pandemic remain alarming (Layelmam et al, 2020) and the socio-economic impacts have been as significant as those identified internationally (Nicola et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of these systems utilizes available data and applies mathematical and/or statistical modeling capable of predicting a future outbreak (14)(15)(16). There were several attempts in different countries to establish a modelling method for the prediction of COVID-19 spread including a group in China which estimated the serial interval for COVID-19 (17), to predict the dynamics of COVID-19 spread (18,19). Applying a mathematical model on the available data, a group showed that lockdown measures were effective in reducing COVID-19 transmission rate and that imported cases have a different dynamic of transmission.…”
Section: Introductionmentioning
confidence: 99%